Evaluación de parámetros fisicoquímicos y organolépticos de yogurt tipo griego con mermelada de mango (Mangifera indica) empleando estabilizantes, Carboximetilcelulosa (CMC) y pectina - Choez Machado, Ximena Estefanía (2025)
This experimental research consists of evaluating the physicochemical and organoleptic characteristics of a Greek-style yogurt with mango jam using stabilizers such as Carboxymethylcellulose (cmc) and pectin. Therefore, it seeks to determine how these stabilizers act on the texture, flavor, aroma and color. For this reason, to evaluate the quality of the final product, physicochemical tests were carried out that included measurements of (pH, ºBrix, titratable acidity) even the best treatment T3 (25% mango jam + Carboxymethylcellulose) mold and yeast analysis was carried out, all treatments have to be established by the INEN 2395 regulations, and organoleptic tests to determine the acceptability of the best treatment was carried out through a survey of 30 semi-trained panelists, reflecting the results in a radial graph. Methodologically, the experimental design will establish formulations of 6 treatments in which a completely random bifactorial design will be used + 2 with contrasts; where the first factor corresponds to the percentage of jam and the second factor corresponds to the type of stabilizers such as carboxymethylcellulose and pectin. To measure the means, a Tukey test at p < 0.05 will be used using the Infostat statistical program.